Perlindungan Hukum Terhadap Pembeli Akibat Tidak Terpenuhinya Kewajiban Pelaku Usaha Dalam Transaksi Belanja Online - Rielia Darma Bachriani; Anggi Aulia Sari (Smart Law Journal, 2024)
One type of buying and selling that takes advantage of advances in internet technology is online buying and selling. Even though there are many advantages, it turns out that online buying and selling can cause problems because many traders make mistakes or break agreements. Because buyers are basically in a weak bargaining position and vulnerable to losses in online transactions, legal protection is very important for buyers. The purpose of this research is to determine the extent of legal protection available to buyers if the seller fails to keep his promises when carrying out online transactions. The methods used in this normative legal research include conceptual approaches and statutory approaches which are correlated with current problems in accordance with legal standards, supported by secondary data in the form of literature from journals, books, the internet and other relevant sources. Based on the research results, it can be said that online buying and selling does not always provide mutually beneficial results for all parties involved, for example the seller may make a mistake or fail to deliver the promised goods. It is important for buyers to understand the regulations governing sales and purchase agreements, especially those relating to online buying and selling or e-commerce, because sellers who fail to carry out or fulfill their responsibilities can be very detrimental to buyers. Mistakes in online purchases are usually resolved amicably or without going to court, and businesses usually accept full responsibility for any negligence, whether intentional or not.